1998
DOI: 10.3354/meps167207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light intensity on the foraging and growth of Atlantic cod larvae:interpopulation difference?

Abstract: ABSTRACT-Studies have been conducted on the geographic variation of growth and survlval among fish populations but little work has been done in this regard on the early larval stages of marine fish. We conducted expenments on larvae from 2 separate populations of Atlantic cod to determine their response to light. P r e h i n a r y experiments conducted in our laboratory suggested that the llght intensity under which larvae were reared may affect the growth performance of Atlantic cod larvae from the Scotian Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 25 publications
3
47
1
2
Order By: Relevance
“…These studies used the frequency of larvae with prey in their guts ('feeding incidence') at different light intensities as an indicator of feeding. The prey concentrations in these and other (Puvanendran & Brown 1998, van der Meeren & Jørstad 2001 investigations on the effect of light on growth and survival in larval cod were very high (50 to 4000 l -1 ) compared to natural conditions. This may have caused the larvae to feed non-visually, and to reach satiation at artificially low light levels, even if visual range was reduced considerably.…”
Section: Encountermentioning
confidence: 52%
See 1 more Smart Citation
“…These studies used the frequency of larvae with prey in their guts ('feeding incidence') at different light intensities as an indicator of feeding. The prey concentrations in these and other (Puvanendran & Brown 1998, van der Meeren & Jørstad 2001 investigations on the effect of light on growth and survival in larval cod were very high (50 to 4000 l -1 ) compared to natural conditions. This may have caused the larvae to feed non-visually, and to reach satiation at artificially low light levels, even if visual range was reduced considerably.…”
Section: Encountermentioning
confidence: 52%
“…Cod larvae are adapted to lower light levels, but the lowest values of roughly 0.005 µmol m -2 s -1 (Huse 1994) appear to be very low and we have used the intermediate value of 1 µmol m -2 s -1 in the model. This parameter will affect feeding rates only when light is limiting, and may vary between stocks experiencing different light intensities during early life (Puvanendran & Brown 1998). It is also likely to improve as the eye develops ontogenetically (Fiksen et al 1998, Job & Bellwood 2000.…”
Section: Encountermentioning
confidence: 99%
“…Light has been correlated with a variety of responses such as growth (Wallace et al 1988;Downing & Litvak 1999), survival (Soderberg 1990;Cerqueira & Brugger 2001), swimming activity (Oppedal et al 2001;Marchesan et al 2005;Johansson et al 2006), cannibalism (Appelbaum & Kamler 2000;Han et al 2005), metabolism (Appelbaum & Kamler 2000), metamorphosis (Puvanendran & Brown 2002), swim bladder inflation (Battaglene et al 1994), and feeding behaviour (Puvanendran & Brown 1998;Noble et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Gardner and Maguire (1998) used only two light intensity treatments and concluded that further research was required to clarify the effect of light intensity on survival and growth, especially with higher intensities. The effect of light intensity on the survival and growth of larvae or juveniles has been studied in flatfish larvae (Blaxter, 1986), cod larvae (Huse, 1994), Australian giant crab larvae (Gardner and Maguire, 1998), larval haddock (Downing and Litvak, 1999), Atlantic cod larvae (Puvanendran and Brown, 2000), sea bass post-lavae (Cuvier-Péres et al, 2001) and juvenile haddock (Trippel and Neil, 2003). Light intensity was also reported to affect swimming activity and feeding (Petrell and Ang, 2001;Almazán-Rueda et al, 2004), cannibalism (Hecht and Pienaar, 1993;Gardner and Maguire, 1998;Kestemont et al, 2003), skin color (Rotllant et al, 2003), physiological hormone (Boeuf and Le Bail, 1989), metabolism (Appelbaum and Kamler, 2000), initiation of ecdysis (Waddy and Aiken, 1991), and metamorphosis (Eagles et al, 1986;Puvanendran and Brown, 2002).…”
Section: Introductionmentioning
confidence: 99%